PENGEMBANGAN KARIER PEGAWAI NEGERI SIPIL PADA BIRO SUMBER DAYA MANUSIA KEPOLISIAN DAERAH SULAWESI TENGAH DI SATUAN LALU LINTAS KEPOLISIAN RESORT PALU - Baktiari, Ni Luh (Katalogis, 2018)
This study aims to identify and analyze the Career Development of Civil Servants in the Bureau of Human Resources Central Sulawesi Police (Central Sulawesi Police), via a qualitative descriptive approach on the basis of the opinion Muenir (1993; 10), which states that there are three indicator career development can be implemented and consists of: 1. Education and training, 2. Promotion and 3. Mutations. Based on the results of research and discussion concluded that in education and training is not maximized are conducted or not fully used as the main requirement in the development of career civil servants (PNS) in the Bureau of Human Resources Central Sulawesi Police, Promotion, is also not maximized done, to the level of the Group IID have passed follow UDKP / UDPI, or PNS Group II D which has been eligible for the UDKP / UDPI can be promoted to the echelon IV (jab Pamin), but in order to be promoted to the echelon III (PNS which rank III D) is not yet implemented ,, for mutations or moved to a new position is also not maximized because it has been the past two years has not happened to the post of new mutations, but mutations merely to terms of promotion, is also the mutation only as confirmation only. This occurs because of the extremely limited opportunities to occupy an echelon III, the Regulation's 22 Year 2010 on STOK where chances of civil servants to occupy echelon III is very limited.